2014
DOI: 10.4103/1477-3163.139450
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epidermal growth factor receptor, p53, Bcl2, vascular endothelial growth factor, cyclooxygenase-2, cyclin D1, human epidermal receptor-2 and Ki-67: Association with clinicopathological profiles and outcomes in gallbladder carcinoma

Abstract: Background:The present study observed the expression levels of epidermal growth factor receptor (EGFR), p53, Bcl2, vascular endothelial growth factor (VEGF), cyclooxygenase-2 (cox-2), cyclin D1, human epidermal receptor-2 (HER-2) and Ki-67 in gallbladder carcinoma (GBC) and their association with clinicopathological profiles and disease outcomes.Materials and Methods:Fifty consecutive samples of cholecystectomy/biopsies from GB bed (archived formalin fixed paraffin embedded tissue blocks of different stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 38 publications
1
3
1
Order By: Relevance
“…We also observed significant somatic mutations in chromatin modifier genes such as SF3B1 , ATRX , CREBBP and EZH2 that have not been reported earlier in gallbladder cancer, indicating potential therapeutic options. Analyzing the potential effects of somatic alterations on survival of gallbladder cancer patients, we observed a trend among patients with wild type TP53 to survive longer than patients with TP53 mutations, which is known to predict failure of chemotherapy in several cancer types 50 and is consistent with previous reports observed in gallbladder cancer 51.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed significant somatic mutations in chromatin modifier genes such as SF3B1 , ATRX , CREBBP and EZH2 that have not been reported earlier in gallbladder cancer, indicating potential therapeutic options. Analyzing the potential effects of somatic alterations on survival of gallbladder cancer patients, we observed a trend among patients with wild type TP53 to survive longer than patients with TP53 mutations, which is known to predict failure of chemotherapy in several cancer types 50 and is consistent with previous reports observed in gallbladder cancer 51.…”
Section: Discussionsupporting
confidence: 90%
“…Like the Doval et al . study, which has shown Ki-67 expression was higher in patients of age group <40 years and patients with poorly differentiated tumor,[ 18 ] the present study has shown that Ki-67 has higher expression <40 years of age and more in females, but the results were not statically significant ( P = 0.308). Ki-67 did not provide any correlation with the biomarker expression CEA, CA-125.…”
Section: Discussioncontrasting
confidence: 64%
“…[ 20 ] and Doval et al . [ 21 ] found marked variation in result. It could be assumed due to the use of different scoring systems adopted by different authors.…”
Section: Discussionmentioning
confidence: 99%